2020
DOI: 10.1111/1556-4029.14531
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Forensically Important Insects Associated with Human Remains in Indiana, U.S.A.*

Abstract: Research documenting insect colonization of human remains is limited in North America, and currently nonexistent for the American Midwest. Such research is essential for forensic entomologists to identify species of research interest in a region. In this study, we collected insects from human remains in 24 cases across Indiana from June 2016 through September 2018. We analyzed species composition across scene type and season. Eight species of blow flies were collected as larvae from human remains, with Phormia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This study provides information about the fly species that colonize cat carcasses in Indiana, which is a significant addition to the field of forensic entomology because L. silvarum had not been collected or identified in previous studies using cats as the animal model [34][35][36]. Additionally, L. silvarum is not a common blow fly species encountered in death investigations or research in Indiana [97,98]. Lucilia silvarum had also rarely been collected in other states within the United States [48,49,69,84,86] or in Europe, with only three reports from human death investigations [11,87].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provides information about the fly species that colonize cat carcasses in Indiana, which is a significant addition to the field of forensic entomology because L. silvarum had not been collected or identified in previous studies using cats as the animal model [34][35][36]. Additionally, L. silvarum is not a common blow fly species encountered in death investigations or research in Indiana [97,98]. Lucilia silvarum had also rarely been collected in other states within the United States [48,49,69,84,86] or in Europe, with only three reports from human death investigations [11,87].…”
Section: Discussionmentioning
confidence: 99%
“…Another finding in the Finland study showed that L. illustris emerged a week earlier, which could give L. illustris a competitive advantage over L. silvarum [11]. In Indiana, P. regina and L. sericata are the dominant species to use in research and colonize remains [98]. Since other blow fly species are dominant in the area of this study, L. silvarum may take advantage of resources early on in the decompositional process before other species arrive or display preferential colonization of small carcasses or certain animal species-specifically cats.…”
Section: Discussionmentioning
confidence: 99%
“…The two samples were morphologically identified down to the genus Lucilia and confirmed molecularly. Molecular analyses were conducted following the methods of Weidner et al (2020). After sequencing, barcodes were compared to NCBI data using BLAST.…”
Section: Species Identificationmentioning
confidence: 99%
“…Less research has been conducted using human cadavers, because of practical and legal constraints. Information regarding insects associated with human remains often comes from casework, and is available for British Columbia [16], Hawaii [17], Texas [18,19], Indiana [20], and Italy [21]. Morgues and autopsies conducted at medical institutes can also provide information pertaining to the insects colonizing human remains [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%